2019
DOI: 10.22207/jpam.13.3.18
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic Profiling Elucidated by 1H- NMR and the Correlation with Antibacterial and Antioxidant Activity of (Cyperus rotundus L) Fermented by Lactic Acid Bacteria

Abstract: Cyperus rotundus (Family Cyperaceae) is used as a natural drug with low cost by different local tribes in the Middle East. In this study, the antioxidant and antimicrobial activity of the fermented C. rotundus extract was determined using different assays including DPPH and FRAP, and antibacterial activity. the 1 H-NMR analysis was carried out for the profiling of bioactive metabolites in the fermented C. rotundus extract. The results demonstrated strong antioxidant activity for DPPH (49.08 µg/mL) and for FRAP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The results were very promising when the antioxidant activity was directly proportional to the anticancer activity with ranged from 4.52 ± 0.57 to 9.85 ± 0.68 μg ml. According to a study by Kadum in 2019 in Iraq, Cyperus rotundus extract after fermentation was demonstrated stronger antioxidant activity for DPPH (49.08 µg/mL) and FRAP (46.95 mmol Fe(II)/g) [17].…”
Section: The Antioxidant Activitymentioning
confidence: 98%
“…The results were very promising when the antioxidant activity was directly proportional to the anticancer activity with ranged from 4.52 ± 0.57 to 9.85 ± 0.68 μg ml. According to a study by Kadum in 2019 in Iraq, Cyperus rotundus extract after fermentation was demonstrated stronger antioxidant activity for DPPH (49.08 µg/mL) and FRAP (46.95 mmol Fe(II)/g) [17].…”
Section: The Antioxidant Activitymentioning
confidence: 98%
“…Using electron microscopy, it was observed that the combined treatment induced damages to the peptidoglycans and cell membrane, generating an increase in membrane permeability and revealing an inhibitory activity against β -lactamase [ 114 ]. Another study found that the fermented extracts of C. rotundus inhibited the growth of P. aeruginosa , B. subtilis , and E. coli [ 115 ]. For such reasons, these extracts may be conceived as a natural remedy against infections caused by pathogenic bacteria.…”
Section: Bioactive Effects: Preclinical Evidencementioning
confidence: 99%
“…Exposure to some OPs has been associated with the possible development of cancer (Adeyinka and Pierre 2020). Fenitrothion residues persist a long time in the environment after application, and are subject to different types of degradation, including photolysis, hydrolysis, and biological degradation (Lacorte and Barcelo 1994; Kadum 2019). Sufficient information exists to characterize fenitrothion as highly toxic to honeybees (Thomson 1982; U.S. Environmental Protection Agency 1987; Kidd and James 1991).…”
mentioning
confidence: 99%